Side-polished SMS based RI sensor employing macro-bending perfluorinated POF - Xuezhi Zhang (Institue of Optics and Electronics, Chinese Academy of Sciences, 2021)
A refractive index (RI) sensor based on perfluorinated plastic optical fiber (PF-POF) is introduced in this paper. The PF-POF as multi-mode fiber was side-polished (SP) to form a macro-bending single-mode-multimode-single-mode (SMS) structure. Both ends of the sensor were closely connected to single-mode quartz optical fiber (SMF). The spectral characteristics of the sensor are measured, analyzed and discussed. The results show that when the length of PF-POF is 8 cm, the macro-bending radius is 3 cm, and the SP-depth is 20 μm. The intensity sensitivity reaches −219.504 dBm/RIU in the range of RI = 1.330 ~ 1.356. A reference is provided for the application of PF-POF in RI sensor in the future. The sensor is featured with low-cost, good flexibility and high efficiency.